ANALISIS FAKTOR-FAKTOR PENYEBAB KENAKALAN REMAJA DI JALAN TADUAN, KELURAHAN SIDOREJO, KEC. MEDAN TEMBUNG - Sani Susanti; Laura Aulia Silalahi; Yahya Rambe; Dinatul Zukriyah; Claudya Morawina Sihombing; Ita Karina (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the forms of juvenile delinquency and the contributing factors among adolescents living on Jalan Taduan, Sidorejo Village, Medan Tembung District, Deli Serdang Regency. A descriptive qualitative approach was employed, involving five adolescents who were directly engaged in various types of delinquent behavior such as smoking, drug abuse, involvement in street fighting, alcohol consumption, and online gambling. Data were collected through field observations and in-depth interviews. The findings indicate that peer influence is the most dominant factor contributing to juvenile delinquency, further reinforced by weak parental supervision, a permissive social environment, curiosity, and easy access to sources of delinquent behavior. The study concludes that strengthening the roles of families, schools, and communities is essential to prevent and reduce the prevalence of juvenile delinquency in the area.